Prevalence, knowledge and attitudes of menopausal symptoms among women aged 40-60 years and their associated factors in a semi urban area, Matara district, Sri Lanka - Perera, Samudra T.; Goonewardena, Sampatha E. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Menopause is naturally created milestone in a women’s life. Every woman experiences unique menopausal symptoms that may be physiological, psychological or both. The aim of this study was to determine the prevalence, knowledge and attitudes of menopausal symptoms among women aged 40-60 years and their associated factors in a semi urban area, Matara district, Sri Lanka. Methods: A descriptive cross-sectional community-based study was carried out among 212 women ages 40-60 years in three selected Grama Niladhari divisions Matara district, Sri Lanka. Data was collected using an interviewer administered questionnaire. A validated menopausal rating scale used to measure menopausal symptoms. Data was analysed using SPSS version 23. A probability of p<0.05 was considered significant. Results: The mean age of menopause of the study population was 47.84 years (SD=4.048). The most prevalent somatic symptoms were hot flushes 157 (74.1%), joint and muscular discomfort 138 (65.1%), sleeping problems 126 (59.5%) and heart discomfort 112 (52.9%). Majority (>50%) reported having psychological symptoms and minority reported urogenital symptoms. All menopausal symptoms were more prevalent and was statistically significant in post-menopausal stage for urogenital symptoms. According to the knowledge categorization, majority (>50%) of the respondents had good knowledge regarding menopause. Mean knowledge score was 68.4±18. Married women and more educated women had better knowledge regarding menopause (p<0.05). Public health midwives were the main source of knowledge. Conclusions: Education, creating awareness and providing suitable interventions can be done to improve the quality of life of women through menopausal transitional period.